2016
DOI: 10.1080/09593330.2016.1186225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of operating conditions on the performances of multichannel ceramic UF membranes for textile mercerization wastewater treatment

Abstract: Textile wastewaters are rated as one of the most polluting in all industrial sectors, and membrane separation is the most promising technology for their treatment and reuse of auxiliary chemicals. This study evaluates the performance of three types of tubular ceramic ultrafiltration membranes differing by mean pore size (1, 2 and 500 kDa) treating textile mercerization wastewater from a textile mill at different operating conditions: cross-flow velocity (CFV) and temperature. Acceptable results were obtained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 23 publications
0
17
2
1
Order By: Relevance
“…Dyes in natural waters reduce their transparency, impede photosynthesis, impair plant and animal growth, affect the solubility of oxygen and the self-cleaning process. There are many conventional (chemical and physical) methods of wastewater treatment reducing the concentration of dye contaminants (Avdicevic et al, 2017;Borges et al, 2016). They are often expensive and cause waste disposal problems.…”
Section: Introductionmentioning
confidence: 99%
“…Dyes in natural waters reduce their transparency, impede photosynthesis, impair plant and animal growth, affect the solubility of oxygen and the self-cleaning process. There are many conventional (chemical and physical) methods of wastewater treatment reducing the concentration of dye contaminants (Avdicevic et al, 2017;Borges et al, 2016). They are often expensive and cause waste disposal problems.…”
Section: Introductionmentioning
confidence: 99%
“…The ceramic membrane was found to be the most demanding of all tested membranes regarding the recovery of its normalized permeate flux. The chemical cleaning procedure is described in detail in (Zebić Avdičević et al, ). Permeate normalized flux was measured after each cleaning step and compared to initial value.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of long-term chemical cleaning with sodium hypochlorite on the tubular ceramic NF membranes was investigated because it is known as the most effective cleaning agent for (organically) fouled ceramic membranes [2,6,17,21]. The permeability and MWCO were tested after 100 h of chemical cleaning with 1% sodium hypochlorite to simulate the cleaning intensity of one year of operation, assuming five days of continuous filtration followed by 1.33 h of chemical cleaning with 1% sodium hypochlorite for 365 days [17].…”
Section: Chemical Cleaningmentioning
confidence: 99%
“…Ceramic membranes have proven to be effective for drinking water treatment [2]. In literature, studies can also be found on the treatment of water streams with a high organic load originating from various industries, such as the treatment of textile industry waste streams, both on the laboratory [1,5,6] and pilot scale [7]. In addition, the pulp and paper industry has interest in the use of ceramic membranes since its wastewater is one of the major sources of industrial water pollution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation